Frequency of fiber-rich food intake and associated factors in a Southern Brazilian population Freqüência do consumo de alimentos fontes de fibras e fatores associados em população do Sul do Brasil - Samanta Winck Madruga; Cora Luiza Araújo; Andréa Dâmaso Bertoldi (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2009)
The objective of this study was to verify the frequency of fiber-rich food intake and evaluate its association with socioeconomic, demographic and behavioral characteristics. A city representative sample was selected and 3,993 subjects (> 10 years) were interviewed. The study used the Block Screening Questionnaire. A majority of subjects - 65.6% (95%CI: 64.2-67.1) - presented an inadequate intake frequency. Adjusted analysis for the overall sample showed an increased risk of inadequate frequency among men, adolescents, people of lower socioeconomic levels, current smokers, those insufficiently active and those having fewer than four daily meals. Age group-stratified analysis showed that among adolescents, living alone was a risk factor; for adults, risk factors were sex (male), current smoker, insufficiently active and fewer than four daily meals and; among the elderly they were male and being a current smoker. A lower socioeconomic level was associated to the outcome in all groups. Although the inadequate frequency of intake is very common in this population, teenagers are at a higher risk, pointing to a need for public health actions targeting this particular age group. Verificar a freqüência do consumo de alimentos fontes de fibras e avaliar sua associação com características sócio-econômicas, demográficas e comportamentais. Foi selecionada amostra representativa da cidade e 3.993 indivíduos (> 10 anos) foram entrevistados. Foi utilizado o instrumento Block Screening. A maioria da amostra, 65,6% (IC95%: 64,2-67,1), mostrou freqüência inadequada de consumo. A análise ajustada para amostra global mostrou risco aumentado de freqüência inadequada entre homens, adolescentes, de menor nível sócio-econômico, fumante atual, insuficientemente ativo e aqueles que faziam menos de 4 refeições/dia. A análise por faixa etária mostrou que entre adolescentes, morar sozinho foi um fator de risco; entre adultos, homens, fumantes, insuficientemente ativos e que realizavam menos de 4 refeiões/dia; e, entre idosos, somente homens e fumantes. O menor nível sócio-econômico associou-se ao desfecho em todos os grupos. Ressalta-se que embora a população apresente alto porcentual do desfecho, chama atenção os adolescentes, sugerindo medidas prioritárias nesta faixa etária.